2012
DOI: 10.1371/journal.pone.0032307
|View full text |Cite|
|
Sign up to set email alerts
|

Serum microRNA Biomarkers for Detection of Non-Small Cell Lung Cancer

Abstract: Non small cell lung cancer (NSCLC) is the leading cause of cancer-related mortality world-wide and the majority of cases are diagnosed at late stages of disease. There is currently no cost-effective screening test for NSCLC, and the development of such a test is a public health imperative. Recent studies have suggested that chest computed tomography screening of patients at high risk of lung cancer can increase survival from disease, however, the cost effectiveness of such screening has not been established. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
120
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(123 citation statements)
references
References 30 publications
2
120
0
1
Order By: Relevance
“…The results prove that specific miRNA signatures in pre-disease plasma samples can predict and discriminate the development of more aggressive disease, like in early metastatic tumours that can be frequently be undetectable by yearly spiral CT surveillance. The highlight of the study was number of deregulated miRNAs decreases with increasing time distance to diagnosis which is against the idea that extended time of sample storage can alter miRNA pattern (Hennessey et al, 2012).…”
Section: How and Why Mirnas Qualify As A Screening Markersmentioning
confidence: 89%
“…The results prove that specific miRNA signatures in pre-disease plasma samples can predict and discriminate the development of more aggressive disease, like in early metastatic tumours that can be frequently be undetectable by yearly spiral CT surveillance. The highlight of the study was number of deregulated miRNAs decreases with increasing time distance to diagnosis which is against the idea that extended time of sample storage can alter miRNA pattern (Hennessey et al, 2012).…”
Section: How and Why Mirnas Qualify As A Screening Markersmentioning
confidence: 89%
“…A negative result was found in 810 out of the 1067 (76%) individuals without lung cancer and in 10 of the 48 (21%) individuals with lung cancer, and the authors suggested that the miRNA test could be used as a first-line screening tool in high-risk individuals. However, the usefulness of miRNAs extends beyond the early detection of NSCLC [89,90]. miRNA panels offer the possibility to differentiate NSCLC from benign lesions and to determine the histological tumour type from a tissue sample [87,91], with sensitivities and specificities within the range of 60-100%.…”
Section: Methods Of Mirna Expression Analysismentioning
confidence: 99%
“…Several miRNA pairs involving miRNAs-106a, miR-15b, miR-27b, miR-142-3p, miR-26b, miR-182, 126#, let7g, let-7i (described above) and miR-30e-5p exhibited a negative predictive value and a positive predictive value of 100%. Notably, a combination of two differentially expressed miRNAs miR-15b and miR-27b, was able to discriminate NSCLC from healthy volunteers with high sensitivity, specificity (Hennessey et al, 2012). Upon further testing on additional 130 subjects, this miRNA pair predicted NSCLC with a specificity of 84%, sensitivity of 100%.…”
Section: Mirnas and Lung Cancermentioning
confidence: 94%
“…These studies indicate that knocking-down of miR-21 expression in cancer cells results in phenotypes important for tumor biology. Hennessey et al (2012) conducted Phase I/II biomarker study to examine the feasibility of using serum miRNA as biomarkers for NSCLC. Examination of miRNA expression levels in serum from a multi-institutional cohort of 50 subjects (30 NSCLC patients and 20 healthy controls) identified differentially expressed miRNAs.…”
Section: Mirnas and Lung Cancermentioning
confidence: 99%